2020
DOI: 10.1002/jmv.25813
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological analysis of COVID‐19 and practical experience from China

Abstract: The rapid spread of the epidemic has aroused widespread concern in the international community. Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) was first reported in China, with bats as the likely original hosts and pangolins as potential intermediate hosts. The current source of the disease is mainly patients infected with SARS-COV-2. Patients in the incubation period may also become sources of infection. The virus is mainly transmitted via respiratory droplets and contact, and the population is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
119
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 50 publications
1
119
0
8
Order By: Relevance
“…Obvious reasons were the governmental orders, travel restrictions, and stay at home orders or guidelines for elderly (>70 years, e.g. in Finland) because COVID-19 can be harmful especially for them [ 49 ]. Our results also indicated that birders try to find new, not overcrowded birding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious reasons were the governmental orders, travel restrictions, and stay at home orders or guidelines for elderly (>70 years, e.g. in Finland) because COVID-19 can be harmful especially for them [ 49 ]. Our results also indicated that birders try to find new, not overcrowded birding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Transmission usually occurs through small droplets from normal breathing, coughing and sneezing, and by aerosols or infected secretions and discharge. 3,4 Additionally, some reports have confirmed the virus's existence in gastrointestinal epithelial cells, raising the possibility of feco-oral transmission. 5 Endoscopy units are currently challenged with many restrictions during this outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Low dose of glucocorticoids was used for a few days here, which was not associated with severe sequelae, when the oxygenation index fell sharply. This treatment could be critical in reversing COVID-19 complications [26,27]. Deteriorating severe patients also received immunoglobulin which could neutralize the pathogens, block the receptors on virus-targeted cells and inhibit production of in ammatory factors.…”
Section: Discussionmentioning
confidence: 99%